Thrombogenesis with continuous blood flow in the inferior vena cava - Diaz, José A.; Hawley, Angela E.; Alvarado, Christine M.; Berguer, Alexandra M.; Baker, Nichole K.; Wrobleski, Shirley K.; Wakefield, Thomas W.; Lucchesi, Benedict R.; Myers, Daniel D., Jr. (Thrombosis and Haemostasis, 2010)
Several rodent models have been used to study deep venous thrombosis (DVT). However, a model that generates consistent venous thrombi in the presence of continuous blood flow, to evaluate therapeutic agents for DVT, is not available. Mice used in the present study were wild-type C57BL/6 (WT), plasminogen activator inhibitor-1 (PAI-1) knock out (KO) and Delta Cytoplasmic Tail (ΔCT). An electrolytic inferior vena cava (IVC) model (EIM) was used. A 25G stainless-steel needle, attached to a silver coated copper wire electrode (anode), was inserted into the exposed caudal IVC. Another electrode (cathode) was placed subcutaneously. A current of 250 μAmps over 15 minutes was applied. Ultrasound imaging was used to demonstrate the presence of IVC blood flow. Analyses included measurement of plasma soluble P-selectin (sP-Sel), thrombus weight (TW), vein wall morphometrics, P-selectin and Von Willebrand factor (vWF) staining, transmission electron microscopy (TEM), scanning electron microscopy (SEM); and the effect of enoxaparin on TW was evaluated. A current of 250 μAmps over 15 minutes consistently promoted thrombus formation in the IVC. Plasma sPSel was decreased in PAI-1 KO and increased in ΔCT vs. WT (WT/PAI-1: p=0.003, WT/ΔCT: p=0.0002). Endothelial activation was demonstrated by SEM, TEM, P-selectin and vWF immunohistochemistry and confirmed by inflammatory cell counts. Ultrasound imaging demonstrated thrombus formation in the presence of blood flow. Enoxaparin significantly reduced the thrombus size by 61% in this model. This EIM closely mimics clinical venous disease and can be used to study endothelial cell activation, leukocyte migration, thrombogenesis and therapeutic applications in the presence of blood flow.
Keywords: Endothelial dysfunction; thrombosis; electrolytic injury; inflammation; animal model